Bus rapid transport system for urban mobility in Ahmedabad: A people’s perception of service quality and performance of BRTS - Minampat, Venkat Ram Reddy; Divi, Sriram; Raghuvanshi, Jyothi Singh (Edelweiss Applied Science and Technology, 2024)
Around the world, bus rapid transit systems are gaining popularity as they are a low investment option compared to rail transport but have facilities that cater to rail transport Numerous Indian cities have chosen the concept under the Jawaharlal Nehru National Urban Renewal Mission Scheme. A quality and secure transportation system was one of the mission’s key goals, therefore bus rapid transit systems were promoted. Everyone wants their commute to be a little faster, in fact wherever we are going is more comfortably than before. Jan Marg Bus Rapid Transit, India’s first top-notch bus rapid system, was introduced in 2009 in Ahmedabad. The Jan Marg system set a benchmark for the country and had an impact upon systems all over India, including recently introduced Rainbow rapid-transit bus system in the twin cities of Pune and Pimpri-Chinchwad. Since May 2013, the Ahmedabad Bus Rapid Transit System has been successfully carrying bus passengers over a designated rapid corridor. With the introduction of Intelligent Transport Management Systems (ITMS), BRTS Transport services become more inclusive in nature. Services delivery became more efficient and qualitative in nature. This study’s aim is to examine the performance of the system based on how users feel about BRTS integrated with ITMS under the improved services they have received under and where there may be even more room for improvement. A questionnaire was made, and passengers’ perspectives were collected and evaluated. The majority of the inquiries revealed that the passengers were satisfied and largely approved of the system. The performance of the system will be enhanced if certain issues are properly addressed and fixed.